(untitled) (Journal of Informatics Education and Research, 2023)
A study on factors influencing workplace happiness and its relationship with job satisfaction, employee retention and work performance. The data was collected through the completion of a questionnaire by five hundred employees. The technique employed in this study to gather information from a sample of 446 respondents was purposeful sampling. Among the methods of data analysis are the following: Multiple linear regression testing, validity and reliability testing, and hypothesis testing, like t-test, F-test and coefficient of determination tests, are the three main methods of testing a research instrument. The research verdict shows that workplace happiness is the most job satisfaction factor (R square = 0.863; beta coefficient = 0.929) that influence the most on work performance (R square = 0.824; beta coefficient = 0.908) among employees. The study outlines the present state of contentment among management professionals and the relationship between contentment and production. When people feel content at work, they are more motivated, engaged, and productive. It is anticipated that this research would raise components of job satisfaction and employee perceptions of organizational support, which will help the company make its people happier at work.